Pengaruh Harga, Kualitas Produk, dan Promosi Terhadap Keputusan Pembelian Konsumen Pada PT Anugrah Packaging Indo Kemasan - Princess Taza Tesalonica; Iswati Iswati; Anis Fitriyasari (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to look at the effect of price, product quality, and promotion on consumer purchasing decisions. The population in this study were all consumers who made purchases at PT Anugrah Packaging Indo Kemasan. Sampling using a non-probability sampling approach and obtained 125 respondents. The data analysis technique uses the Multiple Linear Regression Analysis method. The results showed that, partially (t test) price has a positive and significant effect on purchasing decisions. Product quality has a positive and significant effect on purchasing decisions and promotions also have a positive and significant effect on purchasing decisions. Simultaneous test results (F test) show that price, product quality, and promotion have a positive and significant effect on purchasing decisions.